Strategi Guru dalam Mengembangkan Kemampuan Berbahasa Anak Usia Dini di Lembaga PAUD KB AS-SA’ADAH - Moch. Ainul Yaqin; Rahayu Ningsih; Khofifa Inda Maulidah; Dwi Aminatus Sa’adah (Moral : Jurnal kajian Pendidikan Islam, 2025)
This study aims to describe teachers' strategies in developing early childhood language skills at the AS-SA'ADAH Early Childhood Education Centre. It is known that strategies are importantThis appears to be part of a larger context, likely related to educational development teachers must have ideas on how to design and implement these strategies using a descriptive qualitative approach with data collected through direct observation of learning activities, interviews, and documentation. The analysis was conducted using the Miles and Huberman model, which includes the stages of reduction, presentation, and conclusion drawing. The results of the study show that teachers develop children's language skills through storytelling, interactive conversations, singing, and the use of self-made pictures and simple teaching aids. Based on interviews, these strategies not only enrich the vocabulary of early childhood language but also encourage children to be more active in speaking and interacting with their peers and teachers. Language learning associated with educational play activities has been proven to be more interesting for children in the learning process so that it seems natural, because most children tend to get bored with monotonous learning processes. Thus, children's language skills can grow and develop optimally if a teacher is creative, patient, and communicative learning environment.